How and What has Influenced Cryptocurrency Prices? Economic influences or political Influences - Kurihara, Yutaka (Advances in Social Sciences Research Journal, 2022)
Cryptocurrency has been prevailing gradually with repeating fluctuation in value. Cryptocurrency is not classified as a legal currency but a private financial management system that self-managed and is not managed by central banks or governments. Cryptocurrency is different from any other currency used around the world. Unlike central bank- and government-issued currency, the value of cryptocurrency is able to be inflated as the volume of it has a finite limit. The usage of cryptocurrency enables us to send or receive any amount of currency to anyone at a very cheap cost compared to other monetary instruments. Since the introduction of cryptocurrency, it has received much attention. The trading volume of cryptocurrency has been increasing rapidly although the value has crashed occasionally. Some serious incidents have occurred, however, cryptocurrency may have overcome these situations. How and what has influenced cryptocurrency value has been discussed a lot from the view of economic aspects, however, a common consensus has not yet been reached. For this issue, there is a large difference from stocks or other financial assets or financial instruments. However, there is some possibility that political influences rather than economic influences may have impacts on the prices of cryptocurrency. This study employs U.S.-China trade disputes and examines the effects on prices of cryptocurrency. The results show that political issues along with economic issues, including some asset prices, have some influence on cryptocurrency.